Decide and Conquer : Make Winning Decisions and Take Control of Your Life. - Robbins, Stephen P., 1943- (FT Press Pearson Education [distributor], 2003)
Decide and Conquer brings together all the practical skills you need to make the best possible decisions every day. This quick, concise book identifies every key obstacle to quality decision-making... and shows exactly how to overcome them. Discover how your personality impacts your decision-making... why instincts and experience can lead you astray... how to simplify complicated decisions without oversimplifying them... and much more. You'll use these techniques in your relationships, your finances, your career ... every day, everywhere.